Pengaruh Penerapan Media Pembelajaran Pohon KPK dan FPB dalam Pembelajaran Matematika di Sekolah Dasar untuk Meningkatkan Pemahaman dan Hasil Belajar Peserta Didik - Muspiroh Muspiroh; Faikoh Faikoh; Wardah Roihah (Universitas Palan, 2025)
The purpose of this study is to determine the impact of using FPB and KPK trees, two forms of interactive learning media, on primary school mathematics instruction with the goal of boosting students' intrinsic drive to learn. This study employed classroom action research (PTK), a methodology that contains two cycles, cycle I and cycle II, each of which includes the following steps: planning, carrying out the activity, observing the results, and reflecting on the experience. Approximately thirty fifth graders from SDN Tembong 2 participated in the study. Methods such as observation, interviews, testing, and documentation were employed to gather the data. Learning media in the shape of FPB and KPK trees were the tools utilized in this study. This study's findings demonstrate that fifth graders at SDN Tembong 2 may greatly benefit from learning about fruit trees and vegetables through the usage of KPK and FPB learning media. According to the results of this study, this kind of educational media does a good job of boosting students' comprehension and enthusiasm for studying.